Stylohyoid Complex (Eagle) Syndrome Starting in a 9-Year-Old Boy - Gárriz-Luis, Maite; Irimia, Pablo; Alcalde, Juan M.; Domínguez, Pablo; Narbona, Juan (Neuropediatrics, 2017)
Background There are only four previous pediatric reports of the glossopharyngeal neuralgic form of the stylohyoid complex syndrome. Stylohyoid complex has merely been described as cases of glossopharyngeal neuralgia in children.Case Report A 12-year-old boy came to our hospital because of recurrent episodes of severe cranial pain (9/10) lasting for 5 to 15 minutes. Pain affected the right tonsillar fossa, ear, and mastoid region. Since the start at the age of 9 years, the frequency of painful episodes has progressively increased: when admitted to our clinics 3 years later, the child was having up to five episodes daily in spite of analgesic, antiepileptic, and antidepressant drugs; he had abandoned school and leisure. Between episodes, neurological examination detected only discomfort to pressure on the right tonsillar fossa. Three-dimensional computed tomography images of the skull base showed an elongated right styloid process and bilateral calcification of the stylohyoid ligament. After surgical excision of the right styloid process and of part of the stylohyoid ligament, the glossopharyngeal painful episodes ceased. The patient remains asymptomatic seven years later.Conclusion In spite of its rarity in childhood, this debilitating but treatable syndrome should be kept in mind for the differential diagnosis of recurrent cranial pain in the pediatric population.
Keywords: childhood; Eagle syndrome; glossopharyngeal pain; stylohyoid ligament's calcification; styloid process